Dialectical Effects on Nasalance: A Multicenter, Cross-Continental Study. - Awan, Shaheen N.; Bressmann, Tim; Poburka, Bruce; Roy, Nelson; Sharp, Helen; Watts, Christopher (Journal of Speech, Language & Hearing Research, 2015)
Purpose: This study investigated nasalance in speakers from six different dialectal regions across North America using recent versions of the Nasometer. It was hypothesized that many of the sound changes observed in regional dialects of North American English would have a significant impact on measures of nasalance. Method: Samples of the Zoo Passage, the Rainbow Passage, and the Nasal Sentences were collected from young adult male and female speakers (N = 300) from six North American dialectical regions (Midland/Mid-Atlantic; Inland North Canada; Inland North; North Central; South; and Western dialects). Results: Across the three passage types, effect sizes for dialect were moderate in strength and accounted for approximately 7%–9% of the variation in nasalance. Increased differences in nasalance tended to occur between speakers from distinctly different geographical regions, with the highest nasalance across all passages observed for speakers from the Texas South dialect region. Conclusion: Clinicians and researchers who use perceptual and instrumental measures of speech production should be aware that dialectical and socially acquired speech patterns may influence the acoustic characteristics of speech and may also influence the interpretation of normative expectations and typical versus disordered cutoff scores for instruments such as the Nasometer.